Optimal design of distillation systems with less than N−1 columns for a class of four component mixtures - Cortez-Gonzalez, Jazmín; Segovia-Hernández, Juan Gabriel; Hernández, Salvador; Gutiérrez-Antonio, Claudia; Briones-Ramírez, Abel; Rong, Ben-Guang (Chemical engineering research & design, 2012)
► Optimal design of complex distillation systems with less than N−1 columns. ► Multiobjective optimization of distillation systems. ► Multiobjective genetic algorithm with restrictions coupled to AspenONE Aspen Plus. The optimal design of complex distillation systems is a highly non-linear and multivariable problem, with several local optimums and subject to different constraints. In addition, some attributes for the design of these separation schemes are often conflicting objectives, and the design problem should be represented from a multiple objective perspective. As a result, solving with traditional optimization methods is not reliable because they generally converge to local optimums, and often fail to capture the full Pareto optimal front. In this paper, a method for the multiobjective optimization of distillation systems, conventional and thermally coupled, with less than N−1 columns is presented. We use a multiobjective genetic algorithm with restrictions coupled to AspenONE Aspen Plus; so, the complete MESH equations and rigorous phase equilibrium calculations are used. Results show some tendencies in the design of intensified sequences, according to the nature of the mixture and feed compositions.